Chapter HSE Management for a Sound Work Environment: Strategies for Improving Health Safety and Environmental Indicators through Ergonomic Design Thinking - Santos, Marcello Silva e (InTechOpen, 2017)
The environmental effect of ground-borne vibration and noise generated by urban rail transit systems is a growing concern in urban areas. This chapter reviews, synthesizes and benchmarks new understandings related to railway vibration and associated airborne and ground-borne noise. The aim is to provide new thinking on how to predict noise and vibration levels from numerical modelling and from readily available conventional site investigation data. Recent results from some European metropoles (Brussels, Athens, etc.) are used to illustrate the dynamic effect of urban railway vehicles. It is also proved that train type and the contact conditions at the wheel/rail interface can be influential in the generation of vibration. The use of noise-mapping-based results offers an efficient and rapid way to evaluate mitigation measures in a large scale regarding the noise exposure generated to dense urban railway traffic. It is hoped that this information may provide assistance to future researchers attempting to simulate railway vehicle vibration and noise.